Kyrgyz Republic : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The staff report for the Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on the Kyrgyz Republic focuses on economic developments and policies. The nominal exchange rate has remained broadly stable. Discussions focused on refining the end-September quantitative targets and extending the structural reform agenda. The structural reform agenda will continue to focus on governance, the banking sector, and the electricity sector. Agreement was reached on several key governance-related steps in the mining sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet